Influence on Existing Underlying Metro Tunnel Deformation from Small Clear-Distance Rectangular Box Jacking: Monitoring and Simulation - Chong Ma; Hao Zhou; Baosong Ma (Buildings, 2025)
Rectangular box jacking is widely used in densely developed urban areas. However, when conducted with limited clear distance near existing metro tunnels, it introduces considerable structural safety risks. This study investigates a large-section rectangular box jacking project in Suzhou that crosses a double-line metro tunnel with minimal vertical clear distance. Integrated field monitoring and finite element simulations were conducted to analyze the tunnel’s deformation behavior during various jacking phases. The results show that the upline tunnel experienced greater uplift than the downline tunnel, with maximum vertical displacement occurring directly beneath the jacking axis. The affected zone extended approximately 20 m beyond the pipe gallery boundaries. Both the tunnel vault and ballast bed exhibited vertical uplift, while the hance displaced laterally toward the launching shaft. These deformations showed clear stage-dependent patterns strongly influenced by the relative position of the jacking machine. Numerical simulations demonstrated that doubling the pipe–tunnel clearance reduced the vault displacement by 58.87% (upline) and 51.95% (downline). Increasing the pipe–slurry friction coefficient from 0.1 to 0.3 caused the hance displacement difference to rise from 0.12 mm to 0.36 mm. Further sensitivity analysis reveals that when the jacking machine is positioned directly above the tunnel, grouting pressure is the greatest influence on the structural response and must be carefully controlled. The proposed methodology and findings offer valuable insights for future applications in similar tunnelling projects.